2020
DOI: 10.1002/jmv.26269
|View full text |Cite
|
Sign up to set email alerts
|

Coinfection, coepidemics of COVID‐19, and dengue in dengue‐endemic countries: A serious health concern

Abstract: To the Editor, The WHO has declared coronavirus disease-2019 (COVID-19) outbreak as a global pandemic. 1 The outbreak of COVID-19 caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) has spread in 213 countries across the world. As of 30 June 2020, the total confirmed cases of COVID-19 have reached over 11 million with over half million deaths globally. 2 During the COVID-19 pandemic, dengue cases have been increased in most of the dengue-endemic countries in the world. While COVID-19 causes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
53
0
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(58 citation statements)
references
References 4 publications
0
53
0
5
Order By: Relevance
“…Two clear cases of co-infection have been reported previously in Reunion Island ( Verduyn et al, 2020 ) and in Mayotte of French ( Epelboin et al, 2020 ). Nevertheless possible co-infection also have been noticed in Asia ( Miah and Husna, 2020 ). A study in Bangladesh found that co-infection occurred among 25% out of 20 patients and co-infection was associated with high mortality rate ( Saddique et al, 2020 ) alarming the dengue-endemic countries in the region.…”
Section: Discussionmentioning
confidence: 99%
“…Two clear cases of co-infection have been reported previously in Reunion Island ( Verduyn et al, 2020 ) and in Mayotte of French ( Epelboin et al, 2020 ). Nevertheless possible co-infection also have been noticed in Asia ( Miah and Husna, 2020 ). A study in Bangladesh found that co-infection occurred among 25% out of 20 patients and co-infection was associated with high mortality rate ( Saddique et al, 2020 ) alarming the dengue-endemic countries in the region.…”
Section: Discussionmentioning
confidence: 99%
“…Co-infection with tuberculosis or dengue for example may result in delayed diagnosis and treatment and can further spread infection. 5 Close collaboration with infection control and infectious disease specialists can help minimize these risks.…”
Section: Strategy 2: Identify and Treat Co-infectionsmentioning
confidence: 99%
“…A number of countries with particularly severe COVID-19 epidemics regularly experience dengue epidemics (e.g., Peru, Brazil, and Indonesia), and there have been reports of 2020 being an above-average year for dengue in South America (7). A number of warnings have been raised regarding the potential dangers of overlapping dengue and COVID-19 epidemics; e.g., both diseases can result in similar symptoms and there have been reports of serological cross-reaction, which increases the chance of misdiagnosis (8)(9)(10)(11)(12)(13)(14). At least five cases of dengue-COVID-19 co-infection have been reported, one of which resulted in death by stroke (9,(14)(15)(16)(17)(18).…”
Section: Introductionmentioning
confidence: 99%